KAJIAN NILAI INDEKS GLIKEMIK DAN BEBAN GLIKEMIK BUAH JAMBU BIJI, NANAS, PEPAYA, DAN SEMANGKA DENGAN METODE STANDAR ISO SERTA PENGARUHNYA TERHADAP PASIEN DIABETES MELITUS TIPE 2 - Simon Maringan, Alana
Diabetes mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia due to impaired insulin secretion, insulin action, or both. DM can be classified into four types, namely DM type 1, DM type 2, DM in pregnancy, and prediabetes. Based on estimates from the International Diabetes Federation Organization (IDF), at least 463 million people in the world aged 20-79 years had DM in 2019. The high prevalence of type 2 DM is caused by lifestyle factors, one of which is not paying attention to carbohydrate intake. The value of the glycemic index (GI) and glycemic load (GL) can be used to assess the carbohydrate intake of food, one of which is fruit. Moreover, fruit is one of the food choices that can be used as a snack for type 2 DM patients. Type 2 DM patients need to select more fruits to be consumed based on their GI and GL values to maintain the body's blood sugar levels. This study is a collection of data on the GI and GL values of fruits that are widely consumed in Indonesia, namely guava, pineapple, papaya, and watermelon based on the ISO standard method. The data set was obtained from Google Scholar, Pubmed, and Science direct searches. In addition, it was also explained that fruits that are safe for consumption by type 2 DM patients. Pineapple have varied GI values so that they are included in the low, medium, and high groups, but the GL value of pineapples is included in the low group. Therefore, pineapple remains safe for type 2 DM patients by paying attention to the amount of fruit consumed.